THERMAL CHARACTERISTIC ANALYSIS METHOD OF MOTORIZED SPINDLE BASED ON THERMAL LOAD OPTIMIZATION CORRECTION - MENG LingCong; LI ChenTao; YU Bing; LIU Teng; ZHANG JianJun (Jixie qiangdu)
For the inaccuracy of empirical heat loads for spindle thermal simulations,a thermal simulation analysis method onto motorized spindle unit is proposed.Firstly,the fluid-solid-heat coupling simulation model of the motorized spindle unit is established by Ansys Workbench,with the coolant dynamic heat transfer and thermal resistances of bearing inner-spindle shaft and outer rings-bearing housing being considered.Secondly,based on the simulation model,genetic algorithm is used to optimize and correct the heat generation values of spindle motor/beairngs and ambient heat transfer coefficients.The corrected values above are used as thermal loads for thermal simulation modeling of motorized spindle unit.Based on the model,the dynamic relationship between the heat dissipation power of the coolants and the heat generation power of spindle motor/beairngs is studied.Finally,the model accuracy is verified by the spindle temperature testing experiment.The results show that the optimization correction model can effectively improve the temperature field simulation accuracy of the motorized spindle unit,and the spindle structure and the coolant reach the optimal heat-heating balance when the coolant supply temperature is about 2℃ lower than the ambient temperature.